2020
DOI: 10.1007/978-3-030-53288-8_29
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Solving the BMI Problem in Barrier Certificates Generation

Abstract: Barrier certificates generation is widely used in verifying safety properties of hybrid systems because of the relatively low computational complexity it costs. Under sum of squares (SOS) relaxation, the problem of barrier certificate generation is equivalent to that of solving a bilinear matrix inequality (BMI) with a particular type. The paper reveals the special feature of the problem, and adopts it to build a novel computational method. The proposed method introduces a sequential iterative scheme that is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…We present a weak completeness result of our method, in the sense that a barrier certificate is guaranteed to be found (under some mild assumptions) whenever there exists an inductive invariant (in the form of a given template) that suffices to certify the system's safety. A similar result on completeness is previously provided only by symbolic approaches, yet to the best of our knowledge, not by methods base on numerical constraint solving, e.g., [4,60,61]. Experiments on a collection of examples suggested that our invariant barriercertificate condition recognizes more barrier certificates than existing conditions, and that our DCP-based algorithm is more efficient than directly solving the BMIs via off-the-shelf solvers.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…We present a weak completeness result of our method, in the sense that a barrier certificate is guaranteed to be found (under some mild assumptions) whenever there exists an inductive invariant (in the form of a given template) that suffices to certify the system's safety. A similar result on completeness is previously provided only by symbolic approaches, yet to the best of our knowledge, not by methods base on numerical constraint solving, e.g., [4,60,61]. Experiments on a collection of examples suggested that our invariant barriercertificate condition recognizes more barrier certificates than existing conditions, and that our DCP-based algorithm is more efficient than directly solving the BMIs via off-the-shelf solvers.…”
Section: Introductionsupporting
confidence: 73%
“…The comparison in Table 1 suggests that (1) Our invariant barrier-certificate condition recognizes more barrier certificates than the original (more conservative) condition as implemented in SOSTOOLS. In particular, the lie-high-order example does admit an inductive invariant in the form of the given template, but none of the existing barrier-certificate conditions [4,60,63] -concerning Lie derivatives only up to the first order-recognizes it, since we have L 1 f B(x) = 0 We remark that symbolic methods based on, e.g., quantifier elimination [36], can hardly deal with any of the examples listed in Table 1 due to the prohibitively high computation complexity. Moreover, it would be desirable to pursue a comparison with the augmented Lagrangian method for solving BMIs as proposed in [4], which unfortunately is not yet possible due to the unavailability of the implementation thereof.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations